How do you find g[h(x)] and h[g(x)] given #h(x)=2x-1# #g(x)=3x+4#?
To find g[h(x)], substitute h(x) into g(x) wherever there is an x. So g[h(x)] = g(2x - 1) = 3(2x - 1) + 4 = 6x - 3 + 4 = 6x + 1.
To find h[g(x)], substitute g(x) into h(x) wherever there is an x. So h[g(x)] = h(3x + 4) = 2(3x + 4) - 1 = 6x + 8 - 1 = 6x + 7.
By signing up, you agree to our Terms of Service and Privacy Policy
g(h(x))=6x +1 and h(g(x)) = 6x+7
Basically , this is a substitution exercise.
g(h(x)) = g(2x-1) . Now substitute x = 2x-1 in for x in g(x)
hence g(2x-1) = 3(2x-1)+4 = 6x - 3 + 4 = 6x + 1
Similarly : h(g(x)) = h(3x+4) substitute x = 3x+4 in h(x)
hence h(3x+4) = 2(3x + 4 ) - 1 = 6x + 8 - 1 = 6x + 7
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7